INTEGRASI KERANG HIJAU SEBAGAI BIOFILTER UNTUK MENINGKATKAN PERTUMBUHAN UDANG VANNAMEI DI BUDIDAYA POLIKULTUR - Muhammad Fatchu Rozaq; Andi Rahmad Rahim (Jurnal Perikanan Unram, 2024)
Vannamei shrimp, with its several advantages, is an essential export item for Indonesia. Polyculture technique has demonstrated efficacy in augmenting the growth and efficiency of shrimp production, with output consistently rising. In a polyculture system, green mussels function as biofilters and may assimilate organic materials. This study aims to elucidate the impact of green mussel biofilters on the development of Vannamei shrimp inside a polyculture system. This study was executed over a span of 21 days utilizing a Completely Randomized Design (CRD), incorporating three treatments with three replications, which included varying quantities of green mussels (10, 20, and 30 people) with 10 milkfish, 10 Vannamei shrimp, and 250 g of seaweed. The parameters measured were lead (Pb) concentrations in water, soil, and shrimp, along with the absolute lengths of the cephalothorax, abdomen, and overall length of the shrimp. The findings demonstrated that 20 green mussels were the optimal choice for the growth of Vannamei shrimp, despite the absence of statistically significant differences. In the treatment with 30 green mussels, the lead concentration dropped to 0.06 mg/L in water and 0.62 mg/L in soil, however the minimum lead concentration in shrimp was seen in the treatment with 10 green mussels (0.12 mg/kg).